1971
DOI: 10.1063/1.1659545
|View full text |Cite
|
Sign up to set email alerts
|

Noise Thermometry with the Josephson Effect

Abstract: Thermal noise causes a random frequency modulation of the self-oscillation of a Josephson junction, and the temperature of the noise source can be determined by analysis of the generated signal. We show that a thermometer based on this principle would be theoretically capable of measuring temperatures in the microkelvin range, and describe a prototype thermometer which has recorded noise temperatures down to 0.075 K.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0
1

Year Published

1972
1972
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(49 citation statements)
references
References 10 publications
1
47
0
1
Order By: Relevance
“…The basic idea and the arrangement of the experiment are closely related to that of low-temperature noise thermometry, [35] where small voltage differences appearing across an ohmic resistor are converted by a SC loop with a weak link into Josephson's AC (RF) signal. The resistive behavior of B-NCD observed in the SC transition region ensures, namely, that the current flowing through the sample generates, in the array of weak links, a minute potential gradient and, consequently, oscillating Josephson's supercurrent.…”
Section: Measurement Of Current-induced Josephson Noisementioning
confidence: 99%
“…The basic idea and the arrangement of the experiment are closely related to that of low-temperature noise thermometry, [35] where small voltage differences appearing across an ohmic resistor are converted by a SC loop with a weak link into Josephson's AC (RF) signal. The resistive behavior of B-NCD observed in the SC transition region ensures, namely, that the current flowing through the sample generates, in the array of weak links, a minute potential gradient and, consequently, oscillating Josephson's supercurrent.…”
Section: Measurement Of Current-induced Josephson Noisementioning
confidence: 99%
“…'_.if on T is the basis of the RSQUID noise thermometer. 2 An RSQUID so arranged that it may be used to measure heat current we shall call an RSqUID. An RSqUID may be regarded as a heat-current to frequency converter.…”
Section: The Thermal Rsquidmentioning
confidence: 99%
“…The heat capacity C,,, calculated from C., = n/(fl AT) (2) must be corrected for the addenda c, the contribution to 6",. due to parts other than the specimen, including part of the RSqUID itself.…”
Section: Introductionmentioning
confidence: 99%
“…Kamper and Zimmerman suggested that the subtlety of the Josephson effects could provide a true SQUID-based primary noise thermometer [97]. A Josephson junction is shunted by the low resistance R (in the range 1 lX to 1 mX), forming a resistive SQUID configuration.…”
Section: Magnetic Susceptibility Measurement For a Secondary Thermometermentioning
confidence: 99%